Bi-Ti substituted strontium sodium niobate silver tungsten bronze ferroelectric material with ultrahigh energy storage density and energy storage efficiency under medium electric field and preparation method of Bi-Ti substituted strontium sodium niobate silver tungsten bronze ferroelectric material
Through Bi3+/Ti4+ double-substituted strontium niobate sodium silver filled tungsten bronze ferroelectric ceramic material, combined with cold isostatic press forming technology, the problem of insufficient energy storage density and efficiency of lead-free ferroelectric ceramic materials is solved, and high Energy storage density and efficiency, and avoid lead contamination, it is suitable for a variety of high-power applications.
Patent Information
- Application Number
- CN202411354491.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing lead-free ferroelectric ceramic materials have shortcomings in energy storage density and energy storage efficiency, especially in tungsten bronze structures, it is difficult to have both high energy storage density and high energy storage efficiency, and lead-containing in traditional production processes lead causes environmental pollution. .
Bi3+/Ti4+ double-substituted strontium sodium niobate filled tungsten bronze ferroelectric ceramic material was prepared with ultra-high through the chemical ratio of Sr2-xBixNa0.8Ag0.2Nb5-xTixO15 and combined with cold isostatic pressing technology. Ceramic materials with energy storage density and energy storage efficiency avoid the use of lead.
It achieves high energy storage density and high energy storage efficiency of ceramic materials under medium electric field strength, reduces body defects, and is environmentally friendly, and is suitable for high-power microwave weapons, laser weapons and other fields.
Smart Images

Figure CN119241238A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of tungsten bronze structure ceramic materials, and specifically relates to a Bi-metallic material having both ultra-high energy storage density and energy storage efficiency under medium electric field strength. 3+ / Ti 4+ Double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material and preparation method. Background Art
[0002] Ferroelectric materials have become the most widely used functional materials in various cutting-edge technology fields due to their excellent dielectric, piezoelectric, pyroelectric, ferroelectric and photoelectric effects. They are the core components of new electromechanical devices such as sensors, layered actuators, ultrasonic transducers, ferroelectric memories and pyroelectric infrared detectors. In the field of functional ceramics, the research on improving the piezoelectric properties of ferroelectric materials has always been a hot topic for scientists. The content of PbO or Pb3O4 in the ferroelectric ceramic materials currently used is about 60% to 70%. The lead content causes serious environmental problems in the production, use and even decomposition of ferroelectric materials. Therefore, for the sustainable development of human society, countries around the world have not only begun to research and develop lead-free ferroelectric materials, but also have successively passed relevant laws and regulations to restrict the use of lead-containing ferroelectric materials. At present, the development of a new generation of lead-free and environmentally friendly ferroelectric materials has become a general trend. In recent years, although many domestic and foreign scientific researchers have carried out a lot of research work on lead-free ferroelectric material systems, the results achieved have not yet met the actual needs of mankind. There are many types of tetragonal tungsten bronze structure ferroelectrics, which have broad application prospects in many fields. It is the second largest type of ferroelectric after perovskite structure, with a moderate dielectric constant and very low dielectric loss, and is a promising energy storage material. At present, the energy storage density of tungsten bronze structure energy storage ceramics is lower than that of perovskite structure energy storage ceramics. How to obtain ceramic energy storage capacitors with both high energy storage density and high energy storage efficiency in lead-free tungsten bronze system has become a hot issue. Summary of the invention
[0003] The purpose of the present invention is to provide a Bi with ultra-high energy storage density and energy storage efficiency under medium electric field strength. 3 + / Ti 4+ The invention discloses a double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material, and provides a preparation method thereof with simple process, good repeatability and low cost.
[0004] The Bi provided by the present invention 3+ / Ti 4+ The structural formula of the double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material is Sr 2-x Bi x Na 0.8 Ag0.2 Nb 5-x Ti x O 15 , wherein the value of x is 0.1 to 0.5, and the preferred value of x is 0.3.
[0005] The above Bi 3+ / Ti 4+ The preparation method of the double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material comprises the following steps:
[0006] Step 1: Follow Sr. 2-x Bi x Na 0.8 Ag 0.2 Nb 5-x Ti x O 15 According to the stoichiometric ratio, SrCO3, Ag2O, Na2CO3, Nb2O5, Bi2O3 and TiO2 with a purity of more than 99.00% are weighed respectively, all the weighed raw materials are mixed evenly and put into a nylon jar, zirconium balls are used as grinding balls and anhydrous ethanol is used as ball milling media, after fully mixing and ball milling, they are dried to obtain a raw material mixture.
[0007] Step 2: After pre-calcining the raw material mixture, the mixture is subjected to secondary ball milling, drying and sieving to obtain pre-calcined powder.
[0008] Step 3: sintering the pre-burned powder after granulation, tableting and debinding to obtain the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material.
[0009] In the above step 1, the ball milling time is 20 to 24 hours; the drying temperature is 60 to 80° C., and the drying time is 20 to 24 hours.
[0010] In the above step 2, the pre-firing temperature is 1130-1180° C., and the pre-firing time is 5-8 hours.
[0011] In the above step 2, it is further preferred that the pre-firing temperature is 1150° C. and the pre-firing time is 6 hours.
[0012] In the above step 3, the specific operation is: the pre-burned powder is granulated under the action of polyvinyl alcohol binder, pressed into a cylindrical green body by a powder tablet press, and then cold isostatically pressed at a pressure of 200-220 MPa for 5-7 minutes, then heated to 500°C for debinding, and finally sintered at 1190-1290°C for 2-6 hours.
[0013] In the above step 3, it is further preferred that: the pre-burned powder is granulated under the action of a polyvinyl alcohol binder, pressed into a cylindrical green body by a powder tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes, then heated to 500°C, kept warm for 3 hours for debinding, and finally sintered at 1240°C for 4 hours.
[0014] In the above step 3, the heating rate of the sintering is preferably 2 to 5° C. / min.
[0015] The beneficial effects of the present invention are as follows:
[0016] 1. The present invention adopts Sr2Na 0.8 Ag 0.2 Nb5O 15 Basic system for A / B position Bi 3+ / Ti 4+ Substitution preparation of Sr 2- x Bi x Na 0.8 Ag 0.2 Nb 5-x Ti x O 15 Ceramic materials, through Bi 3+ / Ti 4+ The introduction of makes the ceramic material gradually transform from a normal ferroelectric to a relaxor ferroelectric, which helps to obtain an elongated PE curve and ultimately obtain an energy storage ceramic material with both high energy storage density and high energy storage efficiency.
[0017] 2. In the preparation process of ceramic materials, the present invention adopts advanced cold isostatic pressing technology. The cold isostatic pressing has high density, uniform density, and low stress in the green body, which reduces defects such as green body cracking and delamination. This provides a guarantee for the quality of the ceramics and lays the foundation for excellent experimental results. The raw materials selected by the present invention do not contain heavy metals such as lead and are environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material prepared in Comparative Example 1 and the Bi prepared in Examples 1 to 3 3+ / Ti 4+ XRD pattern of double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material.
[0019] Figure 2 The dielectric constant and dielectric loss diagram of the sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material prepared in Comparative Example 1 at different test frequencies.
[0020] Figure 3 is Bi prepared in Example 1 3+ / Ti4+ The dielectric constant and dielectric loss diagram of the doubly substituted sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material at different test frequencies.
[0021] Figure 4 is Bi prepared in Example 2 3+ / Ti 4+ The dielectric constant and dielectric loss diagram of the doubly substituted sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material at different test frequencies.
[0022] Figure 5 is Bi prepared in Example 2 3+ / Ti 4+ The dielectric constant and dielectric loss diagram of the doubly substituted sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material at different test frequencies.
[0023] Figure 6 The sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material prepared in Comparative Example 1 and the Bi prepared in Examples 1 to 3 3+ / Ti 4+ Unipolar hysteresis loop diagram of double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material under critical breakdown electric field.
[0024] Figure 7 The sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material prepared in Comparative Example 1 and the Bi prepared in Examples 1 to 3 3+ / Ti 4+ Comparison of the effective energy storage density and energy storage efficiency of the double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material under the critical breakdown electric field. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0026] Example 1
[0027] Step 1: Follow Sr. 1.9 Bi 0.1 Na 0.8 Ag 0.2 Nb 4.9 Ti 0.1 O 15According to the stoichiometric ratio, 8.1828g of SrCO3 with a purity of 99.95%, 0.6777g of Ag2O with a purity of 99.7%, 1.2363g of Na2CO3 with a purity of 99.99%, 18.9907g of Nb2O5 with a purity of 99.99%, 0.6793g of Bi2O3 with a purity of 99.99% and 0.2331g of TiO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled in a ball mill at a speed of 401 rpm for 24 hours using zirconium balls as grinding balls and anhydrous ethanol as ball milling media. The mixture was dried at 80°C for 24 hours and ground in a mortar for 30 minutes to obtain a raw material mixture.
[0028] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a resistance furnace, heat it to 1150°C at a heating rate of 3°C / min, keep it warm for 6 hours, cool it naturally to room temperature with the furnace, take it out of the furnace, grind it with a mortar for 30 minutes, and then perform a second ball milling according to the method of step 1, ball mill for 20 hours, then place it in a drying oven at 80°C for 24 hours, grind it with a mortar for another 10 minutes, and pass it through a 120-mesh sieve to obtain pre-calcined powder.
[0029] Step 3: The pre-sintered powder is granulated under the action of a polyvinyl alcohol binder, passed through a 100-mesh sieve, and made into spherical powder particles. The powder particles are placed in a stainless steel mold with a diameter of 11.5 mm, and pressed into a cylindrical body with a thickness of 1.3 mm at a pressure of 6 MPa using a powder tablet press. The cylindrical body is placed in a cold isostatic press, and the cold isostatic press is performed at a pressure of 200 MPa for 5 minutes. The cylindrical body is then placed on a zirconia zirconium plate, and the zirconia zirconium plate is placed in an alumina closed sagger. The temperature is first increased to 500°C at a heating rate of 1°C / min, kept for 3 hours to remove the binder, cooled to room temperature, and then increased to 1240°C at a heating rate of 3°C / min, sintered for 4 hours, and naturally cooled to room temperature with the furnace to obtain Bi 3+ / Ti 4+ Double substituted sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material.
[0030] Example 2
[0031] In step 1 of this embodiment, according to Sr 1.7 Bi 0.3 Na 0.8 Ag 0.2 Nb 4.7 Ti 0.3 O 15According to the stoichiometric ratio, 7.2758 g of SrCO3 with a purity of 99.95%, 0.6735 g of Ag2O with a purity of 99.7%, 1.2286 g of Na2CO3 with a purity of 99.99%, 18.1018 g of Nb2O5 with a purity of 99.99%, 2.0253 g of Bi2O3 with a purity of 99.99%, and 0.6950 g of TiO2 with a purity of 99.99% were weighed respectively. The other steps were the same as those in Example 1 to obtain Bi 3+ / Ti 4+ Double substituted sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material.
[0032] Example 3
[0033] In step 1 of this embodiment, according to Sr 1.5 Bi 0.5 Na 0.8 Ag 0.2 Nb 4.5 Ti 0.5 O 15 According to the stoichiometric ratio, 6.3800 g of SrCO3 with a purity of 99.95%, 0.6693 g of Ag2O with a purity of 99.7%, 1.2210 g of Na2CO3 with a purity of 99.99%, 17.2240 g of Nb2O5 with a purity of 99.99%, 3.3545 g of Bi2O3 with a purity of 99.99%, and 1.1511 g of TiO2 with a purity of 99.99% were weighed respectively. The other steps were the same as those in Example 1 to obtain Bi 3+ / Ti 4+ Double substituted sodium strontium niobate silver filled tungsten bronze ferroelectric ceramic material.
[0034] Comparative Example 1
[0035] According to Sr2Ag 0.2 Na 0.8 Nb5O 15 According to the stoichiometric ratio, 8.6407 g of SrCO3 with a purity of 99.95%, 0.6799 g of Ag2O with a purity of 99.7%, 1.2402 g of Na2CO3 with a purity of 99.99%, and 19.4393 g of Nb2O5 with a purity of 99.99% were weighed respectively. The other steps were the same as those in Example 1 to obtain a sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material.
[0036] The Bi prepared in Examples 1 to 3 above 3+ / Ti 4+The surfaces of the double-substituted sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material and the sodium strontium niobate silver-filled tungsten bronze ferroelectric ceramic material prepared in Comparative Example 1 were ground, polished, ultrasonically cleaned, and silver paste was coated on the upper and lower surfaces respectively, placed in a muffle furnace at 840°C for 30 minutes, and naturally cooled to room temperature. The MiniFlex600 X-ray diffractometer produced by Rigaku Corporation of Japan, the 4294A and E4980A dielectric analyzers produced by Agilent Technologies Co., Ltd., and the ferroelectric tester produced by Radiant Corporation of the United States were used to characterize and test its structure and performance, and the relevant performance parameters were calculated by the following formula:
[0037] Dielectric constant ε r :ε r =4Ct-(πε0d)
[0038] Effective energy storage density W rec :
[0039] Energy storage efficiency η:
[0040] Where: C is the capacitance, t is the thickness of the ceramic sheet, ε0 is the vacuum dielectric constant, d is the diameter of the ceramic sheet, P m is the maximum polarization intensity, P r is the residual polarization intensity, and W is the total energy storage density. Figures 1 to 5 .
[0041] Depend on Figure 1 It can be seen that the ceramic materials prepared in Comparative Example 1 and Examples 1 to 3 all have tungsten bronze structures. Figures 2 to 5 It can be seen that the ceramic material (Bi 3+ / Ti 4+ Unsubstituted) is a typical ferroelectric. In Examples 1 to 3, Bi 3+ / Ti 4+ The substituted ceramic material has enhanced relaxivity and evolved into a relaxor ferroelectric. This is because the ferroelectric active element Ti enters the B position to replace, affecting the polarization behavior of the Nb-O octahedron, the polarization active center of the filled tungsten bronze ceramic material. 3+ / Ti 4+ As the amount of substitution increases, the Curie temperature rapidly moves to a lower temperature. In Example 2, when the value of x is 0.3, the Curie temperature of the prepared ceramic material moves to near room temperature. Figure 6 It can be seen that compared with Comparative Example 1, Bi 3+ / Ti 4+ The breakdown field strength and maximum polarization intensity (P max ) has been significantly improved, and the residual polarization intensity (P r ) decreases; as Bi 3+ / Ti4+ With the increase of the substitution amount, the breakdown field strength of the ceramic material prepared in Example 2 when the value of x is 0.3 reaches the maximum, which is increased from 180 kV / cm in Comparative Example 1 to 400 kV / cm. The increase in the breakdown field strength greatly improves the energy storage density; the maximum polarization intensity (P max ) has been significantly improved, and the residual polarization intensity (P r ) is reduced, and the breakdown field strength is increased, so that the ceramic material obtains a higher effective energy storage density and high energy storage efficiency. Figure 7 It can be seen that the effective energy storage density of the ceramic material prepared in Comparative Example 1 is 1.54 J / cm 3 , the energy storage efficiency is 73.1%, 3+ / Ti 4+ The energy storage density and energy storage efficiency of the ceramic materials prepared in Examples 1 to 3 are significantly improved by double substitution at the A / B positions, and the energy storage density is about 2.73 to 8.30 J / cm 3 , the energy storage efficiency is about 77.9% to 90.5%, especially when Bi 3+ / Ti 4+ When the substitution amount is 0.3, the effective energy storage density of the ceramic material at a medium electric field strength of 400 kV / cm is as high as 8.3 J / cm 3 , the energy storage efficiency is as high as 90.1%. It can be seen that the tungsten bronze structure ceramic material of the present invention has both high energy storage density and high energy storage efficiency, and can be widely used in pulse power systems such as high-power microwave weapons, laser weapons, electromagnetic transmitters, hybrid electric vehicles, etc.
Claims
1. A Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field, characterized in that: The general structural formula of the ceramic material is Sr 2-x Bi x Na 0.8 Ag 0.2 Nb 5-x Ti x O 15 , where the value of x is 0.1~0.
5.
2. The Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 1, characterized in that: The value of x is 0.
3.
3. A method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field as claimed in claim 1, characterized in that: The preparation method comprises the following steps: Step 1: Follow Sr. 2-x Bi x Na 0.8 Ag 0.2 Nb 5-x Ti x O 15 According to the stoichiometric ratio, weigh SrCO3, Ag2O, Na2CO3, Nb2O5, Bi2O3 and TiO2 with a purity of more than 99.00% respectively, mix all the weighed raw materials evenly and put them into a nylon jar, use zirconium balls as grinding balls and anhydrous ethanol as ball milling medium, mix them thoroughly and then dry them to obtain a raw material mixture; Step 2: After pre-calcining the raw material mixture, the mixture is subjected to secondary ball milling, drying and sieving to obtain pre-calcined powder; Step 3: sintering the pre-burned powder after granulation, tableting and debinding to obtain the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material.
4. The method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 3, characterized in that: In step 1, the ball milling time is 20 to 24 hours.
5. The method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 3, characterized in that: In step 1, the drying temperature is 60 to 80° C., and the drying time is 20 to 24 hours.
6. The method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 3, characterized in that: In step 2, the pre-firing temperature is 1130-1180° C., and the pre-firing time is 5-8 hours.
7. The method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 6, characterized in that: In step 2, the pre-firing temperature is 1150° C. and the pre-firing time is 6 hours.
8. The method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 3, characterized in that: In step 3, the pre-burned powder is granulated with a polyvinyl alcohol binder, pressed into a cylindrical body by a powder tablet press, and then cold isostatically pressed at a pressure of 200 to 220 MPa for 5 to 7 minutes, then heated to 500°C for debinding, and finally sintered at 1190 to 1290°C for 2 to 6 hours.
9. The method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 8, characterized in that: In step 3, the pre-burned powder is granulated with a polyvinyl alcohol binder, pressed into a cylindrical body by a powder tablet press, and then cold isostatically pressed at a pressure of 200 MPa for 5 minutes, then heated to 500°C, kept warm for 3 hours for debinding, and finally sintered at 1240°C for 4 hours.
10. The method for preparing the Bi-Ti substituted sodium strontium niobate silver tungsten bronze ferroelectric material with ultra-high energy storage density and energy storage efficiency under medium electric field according to claim 8 or 9, characterized in that: In step 3, the heating rate of the sintering is 2-5° C. / min.
Citation Information
Patent Citations
Sodium strontium niobate material as well as preparation method and application thereof
CN108275748A
Sb<5+> doped strontium sodium silver niobate tungsten bronze ferroelectric ceramic material with high energy storage density and energy storage efficiency and preparation method thereof
CN113024250A
Ho < 3 + > / Ti < 4 + > double-doped strontium sodium niobate silver tungsten bronze ferroelectric ceramic material with high energy storage density and energy storage efficiency and preparation method thereof
CN118619672A
Piezoelectric ceramic
JP2002338352A
Labeling apparatus and labeling method
JP2005075378A
